Modelo estocástico y algoritmos en-línea para el problema de gestión de saldo en caja en el Banco Central - Soto , María (2007)
This paper addresses the problem of adequate management of funds that the Ecuadorian private banks must keep in an account at the Central Bank to guarantee solvency of the Ecuadorian financial system. The idea is to invest a certain amount of these funds in foreign banks to increase profit with a very small risk. Through the use of online algorithms we look for decision-aid models to support the daily process of determining investments abroad. We present a stochastic optimization model to manage the account balance in the Central Bank of Ecuador. It turns out that the deterministic equivalent of our multistage stochastic program is far too large to be computationally applicable, even for relativelysmall time periods. Therefore we investigate the use of heuristic techniques and propose online algorithms. We exhibit the results obtained in numerical simulations.